Staging discomfort : performance and queerness in contemporary Cuba - White, Bretton (University of Florida Press, 2020)
"This volume examines how queer bodies are theatrically represented on the Cuban stage in ways that challenge the state's categorization and homogenization of individuals. Bretton White critically analyzes contemporary performances that upset traditional understandings of what constitutes the ideal Cuban citizenry"--